GAMBARAN TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP KUALITAS PELAYANAN DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH TAMAN HUSADA KOTA BONTANG PERIODE JANUARI 2013 - , RISTA DIRGA AYU ANDINI, Septimawanto Dwi Prasetyo,M.Si.,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pharmacy services is one of the health care, which health care is a human need, consequently expected to provide quality health care. When a good quality of service provided, the patient's expectations were fulfilled. Patient expectations are met or not will determine satisfaction with services provided. Patient satisfaction will affect the existence of pharmacy and patient loyalty. For that we need the evaluation to improve patient satisfaction with care by carrying out research levels of patient satisfaction with quality of care. This research aims to see the level of outpatientsâ satisfaction with quality of care in the Taman Husada Public Hospital Pharmacy Bontang period January 2013 and to see the relationship of patient characteristics on satisfaction. This study is a descriptive cross-sectional research methods. Data collection methods used in the study was a questionnaire and sampling method with purposive sampling. The number of respondents was 117 people with the inclusion criteria were patients with a minimum age of 15 years, is using the installation services in the pharmaceutical and never use the service at least once. Data analysis using gap test and Chi Square test. Data presented in tables and percentages are calculated and visualized in diagrams. The results for the level of satisfaction seen from analysis of the test gap. Gap test results on the reliability dimension is -1.010, -1.235 for responsiveness dimension, -0.950 for assurance dimension, -1.117 for empathy dimension, and -1.083 for tangible dimension. all dimensions showed that the negative value so that patient is not satisfied with the service performance of Taman Husana Public Hospital Pharmacy Bontang. In addition, when viewed from the chi square analysis there was no association between patient characteristics on satisfaction.